UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE AND SHARE (SSCS) PADA MATA PELAJARAN MATEMATIKA - KUSMINI KUSMINI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This research is a dilator behind the low student achievement which can be seen from the test results (daily tests). Based on this, it can also be identified several problems that cause low student achievement, which can be formulated as follows